IMPLEMENTASI PROGRAM PENINGKATAN PROFESIONALITAS RELIGIUS GURU DI SDN BURENGAN 5 - Vanes Desta; Arizka Maufyda Putri; Yeni Anggraini Robiatul Sari; Alfi Laila (LPPM Universitas Cipta Mandiri, 2026)
The religious professionalism of teachers is an important aspect in strengthening the character of students and forming a school culture based on religious values. The phenomenon that occurred at SDN Burengan 5 shows that even though religious programs have been implemented, the level of internalization of religious values in teaching practices and professional behavior of teachers still needs to be improved. Therefore, this study aims to analyze the implementation of the teacher religious professionalism improvement program and its impact on strengthening the school's religious culture. This study uses a descriptive qualitative approach with a focus on the program implementation process. Data were obtained through observation of religious guidance activities, in-depth interviews with the principal and teachers, and analysis of documentation of training and spiritual guidance activities. Data analysis was carried out through the stages of reduction, data presentation, and conclusion drawing to obtain a comprehensive picture of the program's effectiveness. The results showed that the program to improve the religious professionalism of teachers at SDN Burengan 5 was carried out systematically through habituation, training, and leadership support, thereby improving the religious competence and professional behavior of teachers. The discussion confirms that these individual changes developed into a harmonious and consistent strengthening of the school's religious culture, which had an impact on the entire school community. The implementation of the program proved effective in strengthening the religious dimension of teachers' professionalism and shaping a harmonious, religious, and character-building school culture. The success of the program was greatly influenced by the support of school management, collaboration among educators, and the sustainability of coaching activities. These findings confirm that improving teachers' religious professionalism not only strengthens their pedagogical competence but also becomes an important foundation in building an educational environment with integrity and oriented towards moral values.